Hypervalent hydridosilicate in the Na–Si–H system - Spektor, Kristina; Kohlmann, Holger; Druzhbin, Dmitrii; Crichton, Wilson A.; Bhat, Shrikant; Simak, Sergei I.; Vekilova, Olga Yu; Häussermann, Ulrich (Frontiers in Chemistry, 2023)
Hydrogenation reactions at gigapascal pressures can yield hydrogen-rich materials with properties relating to superconductivity, ion conductivity, and hydrogen storage. Here, we investigated the ternary Na–Si–H system by computational structure prediction and in situ synchrotron diffraction studies of reaction mixtures NaH–Si–H2 at 5–10 GPa. Structure prediction indicated the existence of various hypervalent hydridosilicate phases with compositions NamSiH(4+m) (m = 1–3) at comparatively low pressures, 0–20 GPa. These ternary Na–Si–H phases share, as a common structural feature, octahedral SiH62− complexes which are condensed into chains for m = 1 and occur as isolated species for m = 2, 3. In situ studies demonstrated the formation of the double salt Na3[SiH6]H (Na3SiH7, m = 3) containing both octahedral SiH62− moieties and hydridic H−. Upon formation at elevated temperatures (>500°C), Na3SiH7 attains a tetragonal structure (P4/mbm, Z = 2) which, during cooling, transforms to an orthorhombic polymorph (Pbam, Z = 4). Upon decompression, Pbam-Na3SiH7 was retained to approx. 4.5 GPa, below which a further transition into a yet unknown polymorph occurred. Na3SiH7 is a new representative of yet elusive hydridosilicate compounds. Its double salt nature and polymorphism are strongly reminiscent of fluorosilicates and germanates.